The Meaning of Life in Adolescents Who Have Experienced Pregnancy Outside of Marriage - Gokok, Claudia Kewa; Benu, Juliana Marlin Y.; Ruliati, Luh Putu; Damayanti, Yeni (Universitas Nusa Cendana, 2025)
Abstract. Adolescence is a transitional period from childhood to adulthood. It’s atime when individuals have sexual curiosity and interest. Some teenagers are sexuallyactive, while others are not at all. Teenagers who have sex are at risk of experiencingunwanted pregnancies. The purpose of this study was to determine the descriptionof the meaning of life in teenagers who experience pregnancy outside of marriage.This study is a qualitative study with thematic analysis techniques. Sampling in thisstudy utilized purposive sampling, with a sample size of 5 participants. There arefour main themes found: 1) Initial response during pregnancy, 2) Challenges, 3)Experiential Values, and 4) Hopeful Values. It shows that teenagers who are pregnantoutside of marriage find sources of meaning in life through the love given by peoplearound them, spiritual activities, and hope for themselves and their children to havea better life in the future. Keywords: Adolescence, Source of Meaning in Life, Pregnancy Outside of Marriage